2017
DOI: 10.24107/ijeas.305348
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Vibration of CNTs Viscously Damped in Span

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Longitudinal displacement terms in equation (32) will be defined after the solution of longitudinal equation of motion of the nanorod. Longitudinal equation of motion and boundary conditions were obtained in previous studies (Aydogdu and Arda, 2016; Arda and Aydogdu, 2017b) and are written below. The governing equation of motion for longitudinal vibration is and boundary conditions …”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal displacement terms in equation (32) will be defined after the solution of longitudinal equation of motion of the nanorod. Longitudinal equation of motion and boundary conditions were obtained in previous studies (Aydogdu and Arda, 2016; Arda and Aydogdu, 2017b) and are written below. The governing equation of motion for longitudinal vibration is and boundary conditions …”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that the small-scale effect and natural frequencies are inversely proportional. Arda ana Aydogdu [36] studied the longitudinal vibrations of a carbon nanotube (CNT) with an attached damper, taking into account the nonlocal stress gradient elasticity theory. They demonstrated that the nonlocal effects significantly influence the dynamical behavior of a CNT with an attached damper.…”
Section: Introductionmentioning
confidence: 99%
“…Aydogdu (2009b, 2014) proposed the analysis model and studied the longitudinal vibration characteristics of nanorod structure with an attached spring and clamped-free boundary condition. Arda and Aydogdu (2017) investigated the longitudinal vibration of a carbon nanotube attached to a damper by using the nonlocal stress gradient elasticity theory.…”
Section: Introductionmentioning
confidence: 99%